KEPENTINGAN CINA DALAM PEMBANGUNAN PANGKALAN MILITER DI DJIBOUTI PADA TAHUN 2016 - Arif Darmawan; Intan Widya Ningsih (Indonesian Association for International Relations, 2020)
China is not only the most populated country in the world. China's success is so rapidly, especially in the economic field that China so overwhelmed many countries. Entering a new chapter in the 21st century is not only focused on economic, China then renewed its defense policy to strengthen China's sovereignty and achieve its national interests. One of China's strategies was to build its first military base in Djibouti, Africa, in 2016 then. It was a new history for China in its military field. This study aims to analyze the intentions and objectives of China that built its military base in Djibouti using the neorealist theory of Kenneth Waltz. The focus of this research lead to the China’s military base that grown from some factors and the effect on the global order.